Bioactive compounds content and antimicrobial activities of wild edible Asteraceae species of the Mediterranean flora under commercial cultivation conditions - Petropoulos, Spyridon Α. (2018)
Nine wild edible species belonging to Astreaceae family, native to the Mediterranean basin were tested for their chemical composition (phenolic compounds, tocopherols, and organic acids) and antimicrobial activities over two growing periods, apart from Scolymus hispanicus and Hedypnois cretica which were tested for only one growing period. Flavonoids were the most abundant phenolic compounds in all the species, except for the case of Taraxacum species where significant amounts of chicoric acid were detected, while phenolic compounds content increased in the 2nd growing period by 4.6–397.4% for the tested species. α- and β-tocopherols were the main tocopherols, apart from Taraxacum sp. where significant amounts of γ-and δ-tocopherols (18.32 and 16.31 μg/ 100 g fresh weight) were detected, while total tocopherols content either increased (Reicardia picroides, Picris echioides, Urospermum picroides, and Taraxacum officinale) or decreased (Hymenonema graecum, Sonchus oleraceus, Taraxacum sp.) in the 2nd growing period. Oxalic acid was the most abundant organic acid, with the highest content (972 mg/100 g fresh weight) being observed in H. graecum (L.) DC. in the 1st growing period. Moreover, with the exception of H. graecum and S. olearaceus, total organic acids content increased in the 2nd growing period. Significant antimicrobial activities were observed against Bacillus cereus, Salmonella typhimurium and Penicillium ochrochloron for all the studied species. In conclusion, the studied species showed great potential for commercial cultivation, while plant extracts could find use in the food industry as alternative food preservatives.